2007 revised competitveness ranking of Indian States and Union territories with relative competitiveness indices of 66 economies of China and India - Lee, Szu Yung (2008)
This report centers on the study of competitiveness of the 35 States and Union Territories of India by applying the methodology used in the World Competitiveness Yearbook. By segregating India into 35 smaller economic entities, this report aspires to provide policy makers and investors with a micro-level analysis of this huge country, highlighting the disparity between regions.